Lions and tigers and murder, oh my - Swanson, Denise (Swanson, Denise. Devereaux's Dime Store mystery., 2017)
"Handsome private investigator Jake Del Vecchio has rented the office space on the second floor above Devereaux's Dime Store, and Dev now finds herself embroiled in his first case, which involves Gabriella Winston, the missing wife of wealthy philanthropist Elliot Winston. Elliot is determined to open a wildlife park on the edge of town but is facing all sorts of angry opposition -- including Gabriella. After the Winstons have a bitter fight, Gabriella disappears, and their house is ransacked. The authorities are quick to claim Elliot killed his wife, but Dev's not so sure."-- <U+01C2>c provided by publisher.